2018
DOI: 10.1159/000489784
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Lung Cancer in Patients Younger than 40 Years: A Prospective Multicenter Analysis in France

Abstract: Objectives: The aim of this study was to describe the demographic and clinico-pathological characteristics of lung cancer in patients younger than 40 years. Materials and Methods: This was a prospective study performed within the Groupe Français de Pneumo-Cancérologie. Consecutive patients diagnosed with lung cancer before the age of 40 years were eligible. Data on demographics, medical history, clinico-pathological characteristics, treatment and overall survival were analysed. Results: In total, 146 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
(34 reference statements)
7
16
0
Order By: Relevance
“…In our study, 28.83% of the younger group smoked, which is lower than the proportions reported internationally, such as in Japan (47.4–66%) and the USA (80–93%) 12 , 20 , 41 , 42 , 54 56 . Nevertheless, the proportion of smokers in our study is consistent with those reported in Liu's and Hou's studies, with the proportions of lung cancer patients who were smokers reported as 28.40% and 28.81% in China, respectively 34 , 46 , in contrast, the proportion in our study was higher than that in the study by Laurence et al, which reported that approximately 14.0% of the lung cancer patients younger than 40 years in France and Peru were smokers 23 , 57 . A family history of cancer was regarded as a surrogate for a genetic predisposition for lung cancer in some previous studies 24 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, 28.83% of the younger group smoked, which is lower than the proportions reported internationally, such as in Japan (47.4–66%) and the USA (80–93%) 12 , 20 , 41 , 42 , 54 56 . Nevertheless, the proportion of smokers in our study is consistent with those reported in Liu's and Hou's studies, with the proportions of lung cancer patients who were smokers reported as 28.40% and 28.81% in China, respectively 34 , 46 , in contrast, the proportion in our study was higher than that in the study by Laurence et al, which reported that approximately 14.0% of the lung cancer patients younger than 40 years in France and Peru were smokers 23 , 57 . A family history of cancer was regarded as a surrogate for a genetic predisposition for lung cancer in some previous studies 24 .…”
Section: Discussionsupporting
confidence: 92%
“…A Polish study suggested that patients younger than 50 years old were relatively more likely than their older counterparts to have had a mother who had had lung cancer (4.7% vs 3.0%; P < 0.001) and to have had a father who had had lung cancer (7.6% vs 4.1%, P < 0.001) 58 . Another study by Laurence et al reported that the relatives of 25% of the younger patients who had a family history of lung cancer had developed the disease before they were 45 years old, compared to less than 5% in the old group 23 . One study by Abbasowa et al reported that the proportions of the younger and older groups of patients who had a family history of cancer were 44.8% and 36.0%, respectively, and the difference was statistically significant 59 .…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of EGFR mutations varies widely between studies included in this systematic review, probably due to ethnicity and the retrospective nature of the studies. Only seven 11,14,[17][18][19]41,42 out of fourteen studies found statistically significant differences in the prevalence of EGFR mutations across age groups (see Table 1). However, four 12,15,18,19 out of these seven studies found a significantly higher percentage of EGFR mutations among older patients with LUAD.…”
Section: Genomic Profiling In Aya With Lung Cancermentioning
confidence: 99%
“…The disease features and treatment outcomes among young NSCLC patients in the US, Western Europe and East Asia have been frequently studied [6][7][8][9][10][11][12][13][14][15]. Commonly, these comprehensive investigations of single-institutional or multi-centre cancer databases have sought (1) to quantify the rates of driver mutations and/or germline mutations among those with advanced NSCLC and/or (2) to recognise opportunities to explore more aggressive multimodality treatment regimens among those with early-stage diseases.…”
Section: Introductionmentioning
confidence: 99%